Proceedings of the Twelfth ACM International Conference on Web Search and Data Mining 2019
DOI: 10.1145/3289600.3291021
|View full text |Cite
|
Sign up to set email alerts
|

Why the World Reads Wikipedia

Abstract: As one of the Web's primary multilingual knowledge sources, Wikipedia is read by millions of people across the globe every day. Despite this global readership, little is known about why users read Wikipedia's various language editions. To bridge this gap, we conduct a comparative study by combining a large-scale survey of Wikipedia readers across 14 language editions with a log-based analysis of user activity. We proceed in three steps. First, we analyze the survey results to compare the prevalence of Wikipedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 29 publications
(34 reference statements)
2
18
0
Order By: Relevance
“…Finally, we return to our study of global reading behavior. Consistent with the results of Lemmerich et al, we find that readers in countries with lower HDI or in the so-called Global South spend more time reading per page view compared to readers in the Global North or in countries with higher HDI [18]. Moreover, this difference is amplified where we would expect users to consume information in depth: on the desktop (non-mobile) site.…”
Section: Introductionsupporting
confidence: 90%
See 4 more Smart Citations
“…Finally, we return to our study of global reading behavior. Consistent with the results of Lemmerich et al, we find that readers in countries with lower HDI or in the so-called Global South spend more time reading per page view compared to readers in the Global North or in countries with higher HDI [18]. Moreover, this difference is amplified where we would expect users to consume information in depth: on the desktop (non-mobile) site.…”
Section: Introductionsupporting
confidence: 90%
“…They found that readers in lower-HDI countries are more likely to use Wikipedia in educational contexts and for intrinsic learning, but not for fact-checking [18]. Such motivations and contexts are likely to involve longer sessions and dwell times compared to fact-checking [18,32]. Therefore, we predict that readers in lower-HDI countries and in the Global South are more likely to have longer dwell times on Wikipedia articles.…”
Section: Reading Time and Global Contextsmentioning
confidence: 82%
See 3 more Smart Citations